TINGKAT KECERNAAN PROTEIN DAN ENERGI METABOLIS BIJI DURIAN DENGAN METODE PEREBUSAN SEBAGAI PAKAN ALTERNATIF - Krismiyanto, Lilik; Mangisah, Istna; Suthama, Nyoman (Journal Galung Tropika, 2019)
The study aims to examine the protein digestibility and metabolic energy in boiled durian seeds as alternative feeds for broiler chickens. A total of 30 broiler chickens with body weight of 1,476.75 ± 21.15 g, durian seed flour, excreta container, and force feeding were used in this study. The study design used a comparative test (t-test) with each treatment filled 15 tails. The treatments applied included durian seed flour without boiling (T0), and durian seed flour with 30 minutes boiling (T1). The parameters measured were pure metabolic energy values and crude protein digestibility. Data were performed t-test at a probability of 5%. Based on the t-test results obtained that giving of durian seed flour singly by boiling for 30 minutes had a significant effect (P <0.05) on protein digestibility and metabolic energy in broilers. The conclusion were durian seed flour that was boiled for 30 minutes (T1) can increase metabolic energy, so that it can be an alternative source of energy in broiler chicken feed.